Improvement Heavy Oil Transportation IN Pipelines (laboratory study) - Faris, Haidar A.; Abdulrazak, Dr. Ayad A. (Journal of Petroleum Research and Studies, 2017)
Since from the past, drag has been identified as the main reason for the loss of energy in pipelines and other similar transportation channels. The contribution of this drag is due to mainly viscous of the flow as well as friction against the pipe walls. These energy losses can be identified through pressure drop, which will results in more pumping power consumption. Due to their very high viscosity heavy oil cannot be transported as such in pipelines and required additional treatments [1]. This work studied flow increase (%FI) in heavy oil at different flow rates (2 to 10 m3/hr) in two pipes (0.0381 m & 0.0508 m) ID. By using different additives (toluene and naphtha) with different concentrations (2, 4, 6, 8 and 10) %wt at 27ᵒC. The results of this study showed Increasing values of FI % and Maximum Dr% of 40.48% and 37.03 % were obtained using heavy oil containing 10% wt of naphtha flowing in pipes of 0.0508 and 0.0381 m I.D. at 27°C respectively. Increasing values of %Dr with increasing of Reynolds number, fluid velocity and additive concentration, the used additives (toluene and naphtha) reduce the high viscosity of used heavy oil, and naphtha is more efficient as viscosity reducer than toluene. All these results show treatment heavy oil and improvement their transport in pipelines.